GRAPHIC PREPARATION OF JUNIOR SCHOOLCHILDREN IN LESSONS OF LABOR TRAINING (Pedagogy of Higher and Secondary Education, 2004)
In the article is consideration of the question about possibility the lessons of work in taking hold junior schoolchildren of graphic literacy.